Drivers of multi-decadal nitrate regime shifts in a large European catchment. (1st June 2022) - Wachholz, Alexander; Jawitz, James W; Büttner, Olaf; Jomaa, Seifeddine; Merz, Ralf; Yang, Soohyun; Borchardt, Dietrich
Abstract: Long-term monitoring shows evidence of persistent changes in the magnitude and timing of the seasonal pattern of nitrate concentrations in streams, with possibly grave effects on aquatic ecosystems. Seasonal patterns of stream nutrient concentrations are determined by a complex interplay of inputs, transport, and turnover. Over multi-decadal periods, each of these factors may change due to socio-economic factors such as consumption patterns, governance regimes, or technological control measures. Here we test the hypothesis that observed multi-decadal changes in stream nitrate seasonality could be explained by changes in the relative importance of catchment nutrient sources over time. We analyze 66 years of shifting nitrate seasonality in a large, central-European river (Elbe) during a period of significant socio-political changes (1954–2019), with correspondingly significant changes in the sources of anthropogenic nitrate emissions. We develop a mixed-source succession model to test how the multi-decadal evolution of the composition of nitrate sources (point and diffuse) influences in-stream seasonality. We show that the in-stream nitrate seasonality of the River Elbe changed significantly from a weak seasonal pattern with peak concentrations during summer in the 1950s to a strong seasonal pattern with peak concentrations during winter in the 1990s. We link these shifts to a succession of technical and political developments which influence the contribution of point and diffuse sources over time. Such shifts in seasonal concentration patterns can significantly impact the macronutrient (carbon, nitrogen, phosphorus) ratios in rivers, which in turn highly affect the health of aquatic ecosystems.